IDENTIFIKASI POTENSI WILAYAH BERBASIS KOMODITAS UNGGULAN DI KABUPATEN MUNA BARAT - Devi ayu Lestari; Muh. Yani Balaka; Irmawatty Paula Tamburaka (Universitas Halu Oleo, 2022)
The aim of the research is to identify and analyze the leading commodities in the fisheries sector that have the potential to be developed in the West Muna Regency. The data obtained were analyzed using location quotient analysis. The type of data used in this study uses secondary data. The results of the analysis show that the catch fisheries commodities of West Muna Regency which are the superior commodities are demersal fish, mangrove crabs, and sea cucumbers. Among the three leading commodities, mud crab has the highest LQ value of 9,35. These commodities are highly competitive and have the potential to advance and develop to boost the economyof the West Muna Regency.